2021
DOI: 10.1021/acs.jmedchem.1c01289
|View full text |Cite
|
Sign up to set email alerts
|

α/Sulfono-γ-AApeptide Hybrid Analogues of Glucagon with Enhanced Stability and Prolonged In Vivo Activity

Abstract: Peptide drugs have the advantages of target specificity and good drugability and have become one of the most increasingly important hotspots in new drug research in biomedical sciences. However, peptide drugs generally have low bioavailability and metabolic stability, and therefore, the modification of existing peptide drugs for the purpose of improving stability and retaining activity is of viable importance. It is known that glucagon is an effective therapy for treating severe hypoglycemia, but its short hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…67 In order to explore the potential applications of a/sulfono-g-AApeptide hybrids by the use of minimal insertion of sulfono-g-AA residues to stabilize short-acting biologically active peptides, we chose this long and complex glucagon peptide as the target. 28 We tried to exchange a amino acids with sulfono-g-AA and other unnatural residues and combined with extension strategies, including functionalized peptides with polyethylene glycol (PEG) and long fatty acid chains to promote the binding of albumin and extend the in vivo activity, expecting to develop glucagon analogues with enhanced stability and prolonged biological activity (Fig. 8).…”
Section: Agonists Of Glp-1rmentioning
confidence: 99%
See 2 more Smart Citations
“…67 In order to explore the potential applications of a/sulfono-g-AApeptide hybrids by the use of minimal insertion of sulfono-g-AA residues to stabilize short-acting biologically active peptides, we chose this long and complex glucagon peptide as the target. 28 We tried to exchange a amino acids with sulfono-g-AA and other unnatural residues and combined with extension strategies, including functionalized peptides with polyethylene glycol (PEG) and long fatty acid chains to promote the binding of albumin and extend the in vivo activity, expecting to develop glucagon analogues with enhanced stability and prolonged biological activity (Fig. 8).…”
Section: Agonists Of Glp-1rmentioning
confidence: 99%
“…1) 26 and have been employed to tackle some continuing challenges in modulating α-helix-mediated PPIs. 27–33 As a class of proteolytically stable peptidomimetics, sulfono-γ-AApeptides and their related peptide hybrids exhibit unique folding stability by adopting a series of robust helical structures with well-defined hydrogen bond patterns. 34–39 This type of unnatural peptidomimetics has the following advantages: (1) half of the side chains are derived from the chiral groups of canonical amino acids, whereas the other half of the side chains are introduced by sulfonyl chlorides, providing an enormous chemical diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa has attracted considerable attention, but the development of Feleucin-K3 was hampered by its poor serum stability, low selectivity, and insufficient activity to meet the requirements of clinical therapeutics . Our previous studies revealed that the positively charged amino acids were comparatively conserved in AMP, but minor changes in hydrophobicity considerably impacted activity and toxicity. , Therefore, the present study focused on introducing sulfono-γ-AA building blocks with different hydrophobic side chains to alter the hydrophobicity of the residues of Feleucin-K3, as such modification should not induce significant conformational change but could potentially enhance the stability and activity (Schemes and ) . The chosen R 1 groups were benzyl or isobutyl, the side chain of Phe or Leu in the parent Feleucin-K3, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, peptide drug discovery has been challenging partially due to poor plasma stability and membrane permeability . Macrocyclization and the incorporation of nonproteogenic amino acids may be used to enhance some characteristics to construct better drug candidates . Since the constraining linker can influence peptides’ secondary structures and biophysical properties, a comprehensive toolkit has been developed to construct chemically constrained peptides .…”
mentioning
confidence: 99%